Coating strategies using layer-by-layer deposition for cell encapsulation - Oliveira, Mariana B. (2016)
The layer-by-layer (LbL) deposition technique is widely used to develop multilayered films based on the directed assembly of complementary materials. In the last decade, thin multilayers prepared by LbL deposition have been applied in biological fields, namely, for cellular encapsulation, due to their versatile processing and tunable properties. Their use was suggested as an alternative approach to overcome the drawbacks of bulk hydrogels, for endocrine cells transplantation or tissue engineering approaches, as effective cytoprotective agents, or as a way to control cell division. Nanostructured multilayered materials are currently used in the nanomodification of the surfaces of single cells and cell aggregates, and are also suitable as coatings for cell-laden hydrogels or other biomaterials, which may later be transformed to highly permeable hollow capsules. In this Focus Review, we discuss the applications of LbL cell encapsulation in distinct fields, including cell therapy, regenerative medicine, and biotechnological applications. Insights regarding practical aspects required to employ LbL for cell encapsulation are also provided.